Матеріали про використання печер у період трипільської культури - Мацкевий, Л.Г. (Археологія, 2002)
У статті проаналізовано матеріали трипільської культури з печери Вертеба на Тернопільщини (с. Більче-Золоте) та нові знахідки того часу з печерно-скельних ансамблів на території Івано-Франківської (Одаїв XV) і Тернопільської областей (Мельниця-Подільська І і Ланівці IV). Зроблено висновки про використання цих порожнин. До недавнего времени был известен лишь один памятник трипольской культуры, расположенный не под открытым небом, а в пещерно-скальном ансамбле-лабиринте Вертеба близ с. Бильче-Золотое Борщевского р-на Тернопольской обл. В последние годы в данной области зафиксировано еще два объекта на территории этого же района близ с. Лановцы и пгт Мельница-Подольская, а также в 50 км к северо-западу от них близ с. Одаев Тлумачского р-на Ивано-Франковской обл. Как свидетельствует синтез источников, пункты Мельница-Подольская І и Лановцы ІV могли быть краткосрочными пристанищами пастухов, охотников и других поселенцев, а Вертеба и Одаев XV, вероятно, представляли собой культовые центры или места определенных религиозных процедур, или убежища (укрытия) во время разнообразных катастроф, а также военной или другой опасности. Самые ранние материалы фиксируются в Вертебе (жванецкий этап позднего триполья), несколько моложе инвентарь из Мельницы-Подольской І (близок к Поливановому Яру ІІІ), а позднейшие — в Одаеве XV и Лановцах ІV (типа Касперовцы). Памятники датируются от 3000 до 2500—2409 лет до н. э. Благодаря относительной защищенности (закрытости) пещер от действия природных и иных факторов материалы в них сохраняются, как правило, лучше, чем на наземных памятниках. Это даст дополнительные возможности для применения разнообразных методик, технических средств и анализов. Until recent times, the only site of Tripotye culture was situated not under the open sky, but in the rockсаме ensemble-labyrinth Verteba near the village of Bilche-Zolotoye (Borschev district, Ternopil region). Recently, two more objects were fixed on the territory of the same region near the village of Lanovisy and the town of Melnitsa-Podol’skaya, and also 50 km to the North-West from them — near the village of Odayev (Tlumachsky district, Ivano-Frankivsk region). As the synthesis of the sources shows, the points of Melnitsa-Podol’skaya-I and Lanovtsy-IV may have been the short-time havens of shepherds, hunters, and the other settlers; Verteba and Odayev-XV may have been the cult centers ог the sites for definite religious procedures or the sanctuaries (shelters) during the different catastrophes and also military or some other danger. The earliest materials are fixed in Verteba (at the Zhvanets stage of the late Tripolye); the accessory from Melnitsa-Podol’skaya-I is a little bit younger (it is close to Polivanov Yar III). The latest materials are known in Odayev-XV and Lanovisy-IV (Kasperovtsy type). The sites are dated from 3000 to 2500–2400 years BC. Owing to the relative defense of the caves from the influence of natural and other factors, the materials in them are of better safety than on the on-earth sites. This fact gives additional opportunities for applying various methods, technical measures, and analyses.